Measuring the social status of education programmes : applying a new measurement to dual vocational education and training in Switzerland - Bolli, Thomas [Verfasser]; Rageth, Ladina [Verfasser] (My University, 2016)
"This paper proposes a new approach to measuring changes in the social status of education programmes, a type of social status that the literature has greatly neglected so far. We focus on the dual Vocational Education and Training (dual VET) system in Switzerland, which has recently received substantial attention across Europe. We argue that, holding everything else constant, a change in the relative ability of students in an education programme, in relation to the cohort, reflects a change in the social status of that programme. Using PISA scores as a proxy for cognitive ability, we apply this approach to test whether growing knowledge of the education system increases the social status of dual VET in Switzerland. Our results, which focus on immigrant students, confirm that the social status of dual VET increases with these students length of stay in Switzerland, thus reflecting their learning process about the Swiss education system." (Editor, BIBB-Doku)
Keywords: T 4.5 Soziologie; S 1.3.1 Ausbildung im Dualen System; I 2.2.1 Westeuropa; Sozialer Status; Berufsausbildung; Duales System; Inländer; Migrant; Ausbildungswahl; Schweiz